IN THE DEVELOPMENT OF PROFESSIONAL AND PEDAGOGICAL SKILLS EFFECTIVENESS OF PRACTICAL LESSONS - Niyozova Shaxnoza Farxod qizi (Bright Mind Publishing, 2025)
This article presents the role and significance of practical lessons in the development of professional and pedagogical skills of future teachers. The practical application of theoretical knowledge, the formation of pedagogical skills and competencies in students are shown. In addition, the development of such qualities as pedagogical reflection, creativity, culture of communication, and responsibility in the process of practice is analyzed. The article serves to further improve the professional training of future teachers.
Keywords: Professional skills, pedagogical skills, practical lessons, pedagogical competence, innovative methods, reflection, teacher-apprentice system.